2023
DOI: 10.1111/jce.15855
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the relative epicardial connection locations and right‐sided pulmonary vein isolation line for successful pulmonary vein isolation

Abstract: Introduction The presence of an epicardial connection (EC) decreases the success rate of pulmonary vein isolation (PVI); however, the effect of designing isolation lines has not been evaluated. We sought to clarify the effects of designing an anterior line for right‐sided PVI considering the presence and location of the EC. Methods Seventy‐four consecutive patients who underwent initial catheter ablation for atrial fibrillation were retrospectively included in this study. The presence of the EC was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The optimal location of PV isolation line is a matter of concern. Recent literature has highlighted the presence of epicardial connections of PVs in certain cases, which has led to difficulties in successful PV isolation 4,5 . Ishikura et al.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The optimal location of PV isolation line is a matter of concern. Recent literature has highlighted the presence of epicardial connections of PVs in certain cases, which has led to difficulties in successful PV isolation 4,5 . Ishikura et al.…”
Section: Figurementioning
confidence: 99%
“…Recent literature has highlighted the presence of epicardial connections of PVs in certain cases, which has led to difficulties in successful PV isolation. 4,5 Ishikura et al reported a low success rate of first-pass isolation in cases with a broader isolation area encompassing an exit site in the left atrium of the epicardial connection, as identified by activation mapping during sinus rhythm. 4 Although segmental ablation on the PV side facilitates complete PV isolation, it increases the risk of PV stenosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 9 Among ECs, EC through the intercaval bundle (EC‐ICB) may need a carina ablation for PV isolation and reduce the acute and chronic success of PV isolation. 2 , 10 , 11 , 12 , 13 , 14 The carina ablation may increase the risk of PV stenosis 15 and phrenic nerve injury; 16 , 17 therefore, avoiding the carina ablation if possible would be better.…”
mentioning
confidence: 99%
“…The frequency and risk factors for the feared complications related to ablation, like steam pop, cardiac perforation, or esophageal injury, are not well understood for vHPSD 5 . Early clinical studies of vHPSD ablation reported first pass PVI in approximately 50% of cases, while first pass PVI was achieved in greater frequency with both conventional and HPSD RF ablation using recently described approaches such as the “CLOSE Protocol.” 5–7 First pass isolation has been shown to be a powerful predictor of procedural efficacy, 3,8,9 thus a greater understanding of the underlying biophysics of lesions created with vHPSD RF ablation may inform optimization of timing and spacing to further improve outcomes for this new technology.…”
mentioning
confidence: 99%